Love is a funny thing - Lai, Francis 1932-2018 (modcinema, 2009)
While filming in Los Angeles, Henri, a composer of movie soundtracks, falls in love with François, an married actress. They decide to travel across the United States. Their trip will be full of adventures, surprising encounters, emotions, and laughter
Original: Frankreich, Italien 1969
Widescreen
Keywords: Film; DVD-Video